Luxembourg Women in Culture, Business & Travel : a Profile of Luxembourger Women in the Fabric of Society. - Press, World Trade (World Trade Press, 2010)
Women often occupy different roles in a foreign culture. Avoid offensive assumptions and behavior by understanding the position of women in Luxembourger society: their legal rights; access to education and health care; workforce participation; and their dating, marriage, and family life.